Public control over the activities of the State Bureau of Investigation: A comparative analysis: El control público de las actividades de la Oficina Estatal de Investigación: Un análisis comparativo - Gulak, Оlena; Halai , Andrii; Iarmolenko, Iuliia; Spodynskyi, Oleksandr; Kapitanenko, Nataliia (Political Questions, 2023)
The purpose of this work was to analyze the adequate level of legal support for the implementation of public control over the activities of the State Investigation Bureau through the activities of the Public Control Council. To achieve the objective, general scientific and special scientific methods of cognition were used simultaneously, in particular dialectical, logical- formal, analysis and synthesis, systemic-structural, legal-comparative, legal-formal and prognostic. On the basis of a comparative analysis of the legal regulation of the issues of formation and activity of the Public Control Councils in a number of newly created law enforcement bodies, a system of blocks was highlighted, which were the subject of analysis, namely: 1) control over the activity of the body; 2) powers of the Public Control Council; 3) the name of the main area of activity of the Public Council; 4) the object of approval of the Regulations of the Public Council. Everything allowed to conclude which are the «bad» normative constructions, the contradictory norms in the related normative acts and to locate the need for unification of approaches according to the identified structural blocks, which were the object of analysis. In addition, attention is focused on those directions that require further scientific analysis and regulatory optimization.